Public issue of banks bonds case study of Bank Pocztowy S. A. - Kamil Gemra (e-Finanse: Financial Internet Quarterly, 2017)
This article concerns the financing of banking in Poland through public bond issues addressed to individual investors. It is a case study of Bank Pocztowy, which, as one of three banks in Poland, decided to raise capital through the public issue of bonds, the buyers of which were to be individual investors. This article uses the research methodology of case study analysis. In addition, a questionnaire with open questions was used. The purpose of the article is to examine the role of bonds in the public issue process in the financing of private banks in Poland. The results of the research show that it is possible to say that individual investors are interested in diversifying their savings by acquiring bank bonds.
Keywords: G10; 330; bonds; Catalyst; subordinated bonds